Testi e letture della cultura materiale domestica in Russia. Un'introduzione - Emilio Mari (eSamizdat)
In the last years, the humanities and social sciences have increasingly discussed the so-called material turn. The publication of The Social Life of Things, edited by Appadurai in 1986, along with a number of studies by Bourdieu, De Certeau, Douglas, Miller, Löfgren et al., directed the attention of scholars to concepts like materiality, inalienable and consumer goods, ‘career’ and the ‘social life’ of things. Slavic studies have approached this question following another, less straightforward path. Later research by Lotman on byt and the ‘everyday behaviour’ prove a certain ‘densification’ of the object of semiotics and its gradual repositioning from structural linguistics to social and cultural history. However, it was only in the 1990s that scholars began to embrace the new approaches of material culture studies. Working within this methodological framework, the monographic section “Rooms, décor, objects. The intérieur in the Slavic area” reflects upon some fundamental questions from a variety of perspectives: which anthropological and cultural meanings has the intérieur acquired for Slavic people? In which way has the ‘small’ history of the intérieur intersected the ‘big’ political and social history, or the changes in fashion, habits and taste? Moreover, shifting from everyday life to its aesthetic representation: in which ways has the intérieur been deployed in Slavic folklore, figurative art and literatures?